The fall and rise of the Islamic state / Noah Feldman - Moten, Abdul Rashid (IIUM Press, 2009)
When empires and government systems fall, they hardly resurface.Few people are worried about a resurgence of monarchy or communism. However, the governing system i.e. the Islamic state(also democracy), which “died” in 1924 has regained popularity amongst Muslims. How does one explain this puzzle especially to the Western policy makers who are alarmed by the growing clamour for a return to sharÊÑah in the Muslim world? Noah Feldman, Professor of Law at Harvard Law School and an adjunct senior fellow at the Council on Foreign Relations, provides an answer by arguing that misgoverned Muslims yearn for a return to a rule of law, the sharÊÑah, “a just legal system, one that administers the law fairly” ensuring justice to all as exemplified during the golden days of Islam.